Ultrasonographic and endoscopic guidance in diagnosis of Helicobacter gastritis presenting as a mass lesion in a dog: A case report - Gomes, Thomas; Harmon, Cecelia; Nappier, Michael (Frontiers in Veterinary Science, 2022)
This case documents a previously undescribed presentation of Helicobacter spp. gastritis. An 8-year-old female spayed golden retriever with chronic vomiting was found to have a cluster of multiple round, well-defined, hypoechoic foci of varying size surrounded by gas within the lumen of the stomach on ultrasonographic examination. Further endoscopic examination revealed multiple raised mass-like lesions in the fundus on endoscopic examination. Histopathological findings were consistent with Helicobacter spp. infection. The dog was treated with both amoxicillin 400 mg and clarithromycin 180 mg BID for 21 days and omeprazole 20 mg SID for 34 days. After treatment, the vomiting and fundic lesions were resolved on ultrasonographic examination. This case represents a novel gross morphologic presentation for Helicobacter spp. gastritis that responded to appropriate therapy and highlights how early intervention with advanced imaging can aid in diagnosis and treatment.